2015
DOI: 10.1371/journal.pone.0113961
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Magnetic Resonance Imaging of the Optic Nerve Provides Limited Predictive Information on Short-Term Recovery after Acute Optic Neuritis

Abstract: BackgroundIn acute optic neuritis, magnetic resonance imaging (MRI) may help to confirm the diagnosis as well as to exclude alternative diagnoses. Yet, little is known on the value of optic nerve imaging for predicting clinical symptoms or therapeutic outcome.PurposeTo evaluate the benefit of optic nerve MRI for predicting response to appropriate therapy and recovery of visual acuity.MethodsClinical data as well as visual evoked potentials (VEP) and MRI results of 104 patients, who were treated at the Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
(45 reference statements)
0
17
2
1
Order By: Relevance
“…VEP), it is easier to make the differential diagnosis and, therefore, the incidence figures are becoming more reliable since some mimickers of ON can be differentiated from ON. [18][19][20][21] Our study found an incidence of 3.0 per 100,000, which is slightly higher than the earlier incidence 2.4 per 100,000 in Southern Finland from a period 1970 to 1978 when MRI and most of the other ancillary methods were not utilized 22 . It is likely that the incidence of ON has increased slightly more than the figures directly indicate, because of the probably lower number of false positive cases in our present study.…”
Section: Other Diagnoses 21%contrasting
confidence: 66%
“…VEP), it is easier to make the differential diagnosis and, therefore, the incidence figures are becoming more reliable since some mimickers of ON can be differentiated from ON. [18][19][20][21] Our study found an incidence of 3.0 per 100,000, which is slightly higher than the earlier incidence 2.4 per 100,000 in Southern Finland from a period 1970 to 1978 when MRI and most of the other ancillary methods were not utilized 22 . It is likely that the incidence of ON has increased slightly more than the figures directly indicate, because of the probably lower number of false positive cases in our present study.…”
Section: Other Diagnoses 21%contrasting
confidence: 66%
“…9 In terms of the contribution of MRI or electrophysiology tests, poor visual outcome may be associated with more extensive or intra-canalicular lesions in orbital MRI lower VEP amplitude or worse initial visual impairment, although such results were mixed and would require replication. 10 The length of the T2 lesion and the contrast-enhancing lesion of the optic nerve visualized by MRI has been proposed as a prognostic factor of visual recovery after ON, 11 whereas functional magnetic resonance imaging (fMRI) tests can detect abnormalities associated with visual complaints after ON. 12 Regarding visual fields, we found that the MSD was a predictor of the HCVA, but we believe it does not imply causality but just association.…”
Section: Discussionmentioning
confidence: 99%
“…Although the severity of visual loss at presentation or some features of optic nerve magnetic resonance imaging (MRI) are associated with a worse outcome, the accuracy of these parameters is limited to use in clinical practice or clinical trials. 912 Hence, we set out to evaluate visual function after acute ON in a prospective cohort study and to identify predictors of residual visual impairment that may be readily detected and useful in clinical practice or in clinical trials to improve patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, inflammation, demyelination, and axonal loss can be demonstrated by various imaging characteristics [ 4 , 5 , 6 ]. Increased signal intensity on T2WI seen in and around lesions results from inflammation-induced edema or ischemia [ 7 , 8 ]. Abnormal contrast enhancement is seen in active inflammatory or demyelinating lesions as a result of breakdown of the blood-nerve barrier [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased signal intensity on T2WI seen in and around lesions results from inflammation-induced edema or ischemia [ 7 , 8 ]. Abnormal contrast enhancement is seen in active inflammatory or demyelinating lesions as a result of breakdown of the blood-nerve barrier [ 1 , 7 ]. Segmental atrophy of the nerve in chronic lesions is the result of axonal loss [9] .…”
Section: Introductionmentioning
confidence: 99%